Amazonian wood chips as a strategy to change the sensory and chemical characteristics of cachaça - SIMIONI, Síntia Carla Corrêa; GALDINO, Maria Laura Silva; SOUZA, Alexandre Henrique Silas; SANTIAGO, Wilder Douglas; NUNES, Cleiton; PEDROSO, Marcio Pozzobon; CARDOSO, Maria das Graças; BIANCHI, Maria; PINHEIRO, Ana Carla (Food Science and Technology, 2025)
The aim of this study was to evaluate the physicochemical properties, temporal profiles, and consumer acceptability of cachaças aged with different Amazonian woods, namely, cumarurana, jatobá, and louro-vermelho, compared with traditional oak. Cachaças were stored with wood chips in glass containers for 6 months, after which sensory and chemical analyses were conducted. The results revealed that cachaças aged with cumarurana and jatobá had sensory profiles and acceptability similar to those aged with oak, displaying desirable wood and vanilla flavors. In contrast, cachaça aged with louro-vermelho was less accepted due to the detection of off-flavors. The chemical analysis indicated that higher levels of volatile acidity, higher alcohols, dry extract, esters, and aromatic compounds, such as ethyl hexanoate and ethyl octanoate, positively influenced the sensory acceptance of the cachaças. Conversely, a translucent hue and high concentrations of certain alcohols were associated with lower acceptance. The study concludes that cumarurana and jatobá present promising alternatives to oak for cachaça aging, offering new opportunities to diversify flavor profiles and meet consumer demands. The use of Amazonian woods could add value to cachaça production, promoting a unique sensory experience while supporting sustainable practices in the beverage industry.